1981
DOI: 10.1210/jcem-53-3-618
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Insulin Removal Contributes to Hyperinsulinemia in Obesity

Abstract: Peripheral plasma insulin and C-peptide concentrations during oral glucose tolerance tests were measured in 7 severely obese and 12 normal weight nondiabetic subjects. The insulin and C-peptide levels as well as incremental areas under the plasma curves were 2--5 times higher in the obese subjects (P less than 0.05). The C-peptide to insulin molar ratios as well as the relation between incremental areas under the plasma curves of the two peptides were used as relative measures of the hepatic insulin extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(70 citation statements)
references
References 18 publications
3
67
0
Order By: Relevance
“…Fractional hepatic insulin exctraction (FHIE) was estimated by the difference between the incremental AUC of the C-peptide and insulin divided by the incremental AUC of the C-peptide (14).…”
Section: Introductionmentioning
confidence: 99%
“…Fractional hepatic insulin exctraction (FHIE) was estimated by the difference between the incremental AUC of the C-peptide and insulin divided by the incremental AUC of the C-peptide (14).…”
Section: Introductionmentioning
confidence: 99%
“…H yperinsulinemia is a characteristic feature of obesity (1,2). Several studies have shown that insulin hypersecretion (2,3) and impaired insulin clearance are main mechanisms for the increased plasma insulin levels found in obese patients (4). In a study of 14 lean subjects and 15 moderately obese patients, Polonsky et al (3) used the C-peptide deconvolution method (5) and intravenous glucose infusions to quantitate the contribution of insulin secretion and insulin clearance to plasma insulin levels.…”
mentioning
confidence: 99%
“…Several studies reported that insulin resistance explains the strong association between obesity and hypertension (17, 1 8). Hyperinsulinemia, which may be due to insulin resistance and reduced insulin clearance, was also found in obesity and hypertension (5)(6)(7)(8). Therefore, insulin is considered to cause BPelevation by stimulating sodium reabsorption (19) and activation of the sympathetic nervous system in obesity (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Euglycemic insulin clamp procedure Since this method has been previously described in detail (1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14], only the general procedure will be outlined here.…”
Section: Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation